Not all missed opportunities cast the same shadow: Voluntary inaction reduces the "sting" of missed sales promotions. Issue 1 (22nd November 2019) - Ford, Weixing; Andrews, Demetra; Sivaraman, Anuradha; Krishnamurthy, Parthasarathy
Abstract: How do consumers who miss extremely attractive sales promotions respond to merely attractive opportunities they later encounter when prices return to higher levels? The literature on inaction inertia suggests that the more attractive the missed opportunity, the less likely a consumer is to accept the subsequently encountered inferior opportunity, indicating that consumers may stay undecided. Thus, consumers are believed to be negatively influenced by the shadow of the attractive opportunities they missed. This has adverse consequences for both consumer and firm welfare. Yet, we sometimes do see consumers buying even after missing a sale. We draw from the literature on regret and personal responsibility to hypothesize the conditions that would allow the consumer to remain uninfluenced by the attractiveness of the missed opportunity. In three studies, we find support for the idea that personal responsibility for missing the first opportunity allows consumers to be less influenced by its attractiveness when they see a second inferior opportunity compared to conditions in which they were not personally responsible for missing the first opportunity; this bodes well both for consumer and marketer welfare.